Answer:
Step-by-step explanation:
O
3x² - 11x - 4 = 0
a = 3 ; b = -11 , c = -4
[tex]Sum \ of \ roots = \dfrac{-b}{a}=\dfrac{-(-11)}{3}=\dfrac{11}{3}\\\\Product \ of \ roots =\dfrac{c}{a}=\dfrac{-4}{3}\\\\[/tex]
W
8x² + 12x = -1
8x² + 12x + 1 = 0
a = 8 ; b = 12 ; c = 1
[tex]Sum \ of \ roots =\dfrac{-b}{a}=\dfrac{-12}{8}=\dfrac{-3}{2}\\\\Product \ of \ roots = \dfrac{c}{a}=\dfrac{1}{8}[/tex]
L
x² + x = 6
x² + x - 6 = 0
a = 1 ; b= 1 ; c = -6
[tex]Sum \ of \ roots = \dfrac{-1}{1}=-1\\\\Product \ of \ roots = \dfrac{-6}{1}=-6[/tex]
G
x²- 2x - 2 =0
a = 1 ; b = -2 ; c = -2
[tex]Sum \ of \ roots = \dfrac{-(-2)}{1}=2\\\\Product \ of \ roots = \dfrac{-2}{1}=-2[/tex]
E
4x - 5 = -4x²
4x² + 4x - 5 = 0
a = 4 ; b = 4 ; c = -5
[tex]Sum \ of \ roots = \dfrac{-4}{4}=-1\\\\Product \ of \ roots=\dfrac{-5}{4}[/tex]
B
12x² +x -6 = 0
a = 12 ; b = 1 ; c = -6
[tex]Sum \ of \ roots =\dfrac{-1}{12}\\\\Product \ of \ roots =\dfrac{-6}{12}=\dfrac{-1}{2}[/tex]
R
2x² + 5x - 25 = 0
a = 2 ; b = 5 ; c = -25
[tex]Sum \ of \ roots=\dfrac{-5}{2}\\\\Product \ of \ roots =\dfrac{-25}{2}[/tex]
A
6x² -5x - 4 = 0
a = 6 ; b = -5 ; c = -4
[tex]Sum \ of \ roots =\dfrac{-[-5]}{6}=\dfrac{5}{6}\\\\Product \ of \ roots = \dfrac{-4}{6}=\dfrac{-2}{3}[/tex]